EFEKTIVITAS PENGGUNAAN QRIS DALAM MENGHIMPUN DANA ZIS DI MASA PANDEMI COVID-19: Studi Kasus LAZ Inisiatif Zakat Indonesia - Lutvia Handiasti (2022)
The government has implemented a large-scale social restriction (PSBB) policy to anticipate the spread of the Covid-19 virus in Indonesia, which has an impact on people's income. The optimization of ZIS collection is expected to support the Government's program in overcoming various community problems that have become a pandemic. The existence of the PSBB policy requires various OPZs to assist in collecting ZIS funds. Centralization of QR codes from various digital payment platforms is needed to optimize ZIS fundraising, especially during the pandemic. Therefore, this study aims to measure the effectiveness of using QRIS as a centralized QR code in collecting ZIS funds during the pandemic. This study uses a descriptive qualitative research method with a case study type. The data collection techniques used are structured interviews, non-participant observation, and documentation using triangulation as a data validity test technique. Furthermore, the data were analyzed using data reduction, data presentation, and drawing conclusions/verification. The results of this study indicate that the use of QRIS at Laznas IZI has not been effective, according to the benchmarks of accuracy and objectivity, as well as timeliness because most of the donors and partners of Laznas IZI are still accustomed to using bank transfers. This research is expected to provide input and recommendations for regulators and zakat management practitioners in an effort to optimize digital platforms, especially with QRIS in collecting ZIS funds.